Axon tract formation in Gli3 conditional mutant mice - Amaniti, Eleni Maria (The University of Edinburgh, 2014)
The cerebral cortex is the largest subdivision of the human brain and is associated with higher cognitive functions. These functions are based on the interconnections between the neurons that form pre- and postnatally in the different telencephalic regions. The processes of neurons with similar functions and connectivity follow the same course and form axon tracts. There are three main axons tracts analysed in this thesis the corpus callosum, the corticothalamic/thalamocortical tracts and the lateral olfactory tract that transfers olfactory information to the telencephalon. In the mouse, these tracts are generated during embryogenesis as axons project to their target area. The mechanisms by which axons navigate still need to be elucidated. Studies of a number of mutant mice have shown that axon pathfinding is under the control of genes. Gli3 is a zinc finger transcription factor with known roles in axon pathfinding. Gli3 is widely expressed in progenitor cells of the dorsal and ventral telencephalon complicating the elucidation of the molecular mechanisms by which Gli3 controls axon tract formation. My aim here is to investigate the spatial and temporal requirements for Gli3 in axon pathfinding in the forebrain using Gli3 conditional mutants as a tool. Regarding the corpus callosum, my findings demonstrated a crucial role for Gli3 in the dorsal telencephalon, but not in the septum or medial ganglionic eminence, to control corpus callosum formation and indicated that defects in the formation of the corticoseptal boundary affect the positioning of callosal guidepost cells. Moreover, conditional inactivation of Gli3 in dorsal telencephalic progenitors led to few corticothalamic axons leaving the cortex in a restricted lateral neocortical domain. This restricted entry is at least partially caused by an expansion of the piriform cortex, which forms from an enlarged progenitor domain of the ventral pallium. Transplantation experiments showed that the expanded piriform cortex repels corticofugal axons. Moreover, expression of Sema5B, a chemorepellent for corticofugal axons produced by the piriform cortex, is similarly expanded. Hence, control of lateral cortical development by Gli3 at the progenitor level is crucial for corticothalamic pathfinding. Finally, by using Emx1Cre;Gli3fl/fl mutants I analysed the consequences of the expansion of the piriform cortex on the formation of the lateral olfactory tract (LOT). This analysis showed that LOT axons also appear to be medially shifted with LOT collaterals aberrantly colonising the expanded piriform cortex. Time course analysis confirmed an expansion of the paleocortical primordium from E13.5 onwards, coinciding with the arrival of the LOT axons. Hence, it is possible that the expanded piriform cortex contributed to the medial shift of the LOT. In conclusion, these findings support a strong link between Gli3 controlled early patterning defects and axon pathfinding defects and form the basis for future analysis of the molecular mechanisms by which Gli3 controls axon pathfinding in the forebrain. My findings also reveal how alterations in GLI3 function may contribute to connectivity defects in human patients with mutations in GLI3.
Analysis of axon tract formation in Gli3 conditional mutant mice
Keywords: Gli3; piriform cortex; corpus callosum; corticothalamic tract